A importância da Educação Ambiental nos anos iniciais do Ensino Fundamental - ARANHA, Priscila do Socorro Santos (2024)
This research analyzes environmental education practices in the early years of elementary school in the context of the National Common Core Curriculum - BNCC. Environmental education is a much-discussed topic at the moment, as the greatest concern is with the preservation and conservation of nature, as a fundamental condition for promoting and guaranteeing quality of life. In the early years of elementary school, environmental education plays a fundamental role in building a society that is more committed to preserving the environment. It also prepares children to be aware and responsible citizens, capable of making decisions that promote environmental protection and guarantee a sustainable future for generations to come. In this context, the aim of this work is to analyze the importance of Environmental Education according to the main references on the subject. This is a literature review, with a survey of articles, monographs and others, with an exploratory investigative method, in order to verify the relevance of implementing EE (Environmental Education) in the early years of elementary school. This study examined 39 articles published between 1986 and 2023, investigating Environmental Education in school settings. Key concerns emerged regarding teacher challenges and the utilization of didactic resources in the teaching-learning process.